Spiritual Competency and Its Impact on Job Satisfaction Among Employees : A Qualitative Exploration from the Employee Perspective - Teguh Iman Santoso (Asosiasi Dosen Peneliti Ilmu Ekonomi dan Bisnis Indonesia (ADPEBI), 2026)
This study examines the role of spiritual competency in enhancing job satisfaction among employees at Perumda Dharma Jaya, an Indonesian public enterprise, through a qualitative phenomenological approach. Focusing on employee perspectives, it explores how spiritual values—such as empathy, ethical alignment, and resilience—mediate workplace dynamics amid high job demands and public accountability. Data were collected via semi-structured interviews and observations from four participants across managerial, supervisory, and operational roles. Findings reveal that spiritual competency fosters job satisfaction by aligning personal and organizational values, yet inconsistencies in policy-practice integration and cultural inclusivity emerged as critical challenges. The study underscores the need for context-specific HR strategies that balance spiritual values with professional expectations, offering actionable insights for public sector organizations to improve employee well-being and organizational outcomes.